2011
DOI: 10.1002/ejsp.824
|View full text |Cite
|
Sign up to set email alerts
|

Are sexualized women complete human beings? Why men and women dehumanize sexually objectified women

Abstract: Focusing on the dehumanization of sexually objectified targets, study 1 tested the extent to which objectified and non-objectified male and female publicity photos were associated with human compared to animal concepts. Results conrmed the hypothesis that, among all targets, only objectied women were associated with less human concepts. This pattern of results emerged for both male and female participants but likely for different reasons. Study 2 directly looked at female and male participants’ afnity with sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
341
3
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(388 citation statements)
references
References 32 publications
34
341
3
8
Order By: Relevance
“…First of all we wanted to highlight that both senses of humanness are complementary and that none has a privileged area of research. While the terms objectification and technical dehumanisation as used in medical practice may recall the association of others with automata or robots, recent research has demonstrated the existence of the denial of uniquely human attributes in both cases (see Vaes, Paladino, & Puvia, 2011;Vaes & Muratore, 2011). A more important variable that determines whether people will differentiate between groups in terms of one or the other sense of humanness consists in one's culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all we wanted to highlight that both senses of humanness are complementary and that none has a privileged area of research. While the terms objectification and technical dehumanisation as used in medical practice may recall the association of others with automata or robots, recent research has demonstrated the existence of the denial of uniquely human attributes in both cases (see Vaes, Paladino, & Puvia, 2011;Vaes & Muratore, 2011). A more important variable that determines whether people will differentiate between groups in terms of one or the other sense of humanness consists in one's culture.…”
Section: Discussionmentioning
confidence: 99%
“…However, objectification is often linked to gender and it suffices to note the frequent associations between animals and sexy women: ''they really are animals'', ''they are panthers [eating rich old men], or cougars [eating younger men]''. Measuring the human-animal dimension, Vaes, Paladino, and Puvia (2011) indeed showed that sexually objectified women were dehumanised. In a similar vein, technical dehumanisation as used in medical practice may recall the association of others with automata or robots.…”
Section: Dimensions Of Dehumanisationmentioning
confidence: 99%
“…Supporting this notion, appearance focus increases objectification, but person focus has the opposite effect; when perceivers focus on the personhood of a female they attribute her more warmth and competence than when they focus on her physical appearance (Heflick and Goldenberg 2009;. Building on prior work that has primarily focused on the dehumanizing consequences of objectification suggesting objectified women are regarded as less warm and competent (Heflick and Goldenberg 2009;; see also Loughnan et al 2010;Vaes et al 2011), we focused on the inverse-whether humanization causes less objectification. Consistent with this idea, humanizing information about the warmth and competence of sexualized women causes people to perceive women in less objectifying and more humanizing ways (e.g., seeing women in more holistic rather than piecemeal ways; Bernard et al 2015).…”
Section: Humanizationmentioning
confidence: 98%
“…The current study examines a situational variable-alcohol consumption-to determine whether intoxication increases objectifying gazes as well as interacts with perceived attractiveness, warmth, and competence to influence objectifying gazes directed at female targets. Furthermore, most studies examining objectification perpetration have focused on very attractive women (e.g., swimsuit models; Bernard et al 2012;Loughnan et al 2010;Vaes et al 2011;celebrities;Heflick and Goldenberg 2009). As a result, less is known about when and why people objectify women who are less attractive, even though average and less attractive women self-report objectification (Kozee et al 2007;Swim et al 2001).…”
Section: Overview and Hypothesesmentioning
confidence: 99%
“…Sexual objectification may be represented on a continuum with more blatant acts and violence, such as assault, exploitation, and trafficking falling on one end and more subtle and covert acts, such as objectifying gazes, inappropriate sexual innuendo, and appearance compliments falling at the other end. Representing a form of body reduction (Langton, 2009), sexual objectification emerges when people focus on women's appearances, bodies, sexual body parts, or sexual functions more than their faces and other non-observable attributes, such as thoughts, feelings, and desires (e.g., Loughnane al., 2010;Vaes, 2011, see also Archer, 1983.…”
Section: Objectificationmentioning
confidence: 97%